Loneliness and cannabis use among older adults: findings from a Canada national survey during the COVID-19 pandemic - Lun Li; Qian (Claire) (BMC, 2024)
Abstract Background Cannabis use has been increasing among older adults in Canada, particularly during the COVID-19 pandemic. This study aims to examine the association between loneliness and cannabis use among older Canadians during the pandemic. Methods Quantitative data analyses were performed based on 2,020 participants aged 55 years and older from the Canadian Perspectives Survey Series 6, 2021: Substance Use and Stigma During the Pandemic. Results This study found that participants who used cannabis in the 30 days before the survey reported significantly higher loneliness scores than those who never used cannabis after adjusting social-demographic, social interaction, and pandemic-related factors. Participants who kept using cannabis during the pandemic also reported significantly higher loneliness scores than those who never used cannabis. Conclusion The findings about the correlation between cannabis use and greater loneliness contribute to the discourse on potential health and wellbeing harms of cannabis use among older adults.